Pelatihan penulisan modul Hybrid mata pelajaran Bahasa Indonesia di era pandemi Covid-19 - Nurbaya, St.; Suhardi, Suhardi; Nurhadi, Nurhadi; Sari, Esti Swatika; Lestyarini, Beniati; Isnan, Faisal (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2023)
The use of technology is an important part of the learning process. Teachers are required to be able to utilize technology optimally and effectively. This demand has been strengthened since the covid-19 pandemic, which requires education to be able to adapt and accelerate quickly. Innovative activities that can be carried out are in developing teaching materials, one of which is hybrid modules. This activity is focused on giving training for middle and high school teachers on the use of barcode, fliphtml5 and flipbook applications, which can support teachers in converting conventional modules into digital or hybrid modules. A total of 90 participants took part in training activities 2 days through an online training by zoom meeting platform for the provision of materials and tutorials; guidance and assistance in making application products through WhatsApp groups consultations; and online meeting forums by zoom meetings for product presentations and reviews. This activity produced 55 digital modules. Participants' responses through the questionnaire stated that they were very satisfied and expected the training to be re-conducted for other teaching and learning innovations.